The role of neuroendocrine pathways in prognosis after stroke. (February 2014) - El Husseini, Nada; Laskowitz, Daniel T
<x xml:space="preserve">Abstract</x> A number of neuroendocrine changes have been described after stroke, which may serve adaptive or deleterious functions. The neuroendocrine changes include activation of the hypothalamo–pituitary–adrenal axis, sympathetic nervous system and alterations of several hormonal levels. Alterations of the HPA axis, increased catecholamines, natriuretic peptides and, decreased melatonin and IGF-1 levels are associated with poor post-stroke outcome, although there is no definitive proof of causality. Therefore, it remains to be established whether alteration of neuroendocrine responses could be used as a potential therapeutic target to improve stroke outcome. This article gives an overview of the major neuroendocrine pathways altered by stroke and highlights their potential for clinical use and further neurotherapeutic development by summarizing the evidence for their association with stroke outcome including functional outcome, post-stroke infection, delirium, depression and stroke-related myocardial injury.